Performance of four varieties of sorghum (sorghum vulgare) at two nitrogen levels - Zainal Abidin, Mohd Idris; Banta, Michael Gregory Timfrick (Penerbit Universiti Kebangsaan Malaysia, 1979)
Four sorghum varieties; Dobbs, CE/71, CE/178 and 655N that were recommended in Satawak were evaluated for yield and other agronomic traits at the Universiti Pertanian Malaysia, Semenggok, Sarawak. The studies also compared two different levels of nitrogen application -84 and 101 kg/ha. The experiment showed no significant differences in grain yield or the other agronomic traits among thesefour varieties. likewise, there was no significant effect in these traits by varying the nitrogen fertilizers at the two levels. However, it is premature to make any conclusive recommendation until more experiment could be laid out with studies to include more varieties, seasonal effects and more variation in the nitrogen rate.